Disputas oligárquicas: as práticas políticas das elites mato-grossenses 1892-1906 - Arruda, Larissa Rodrigues Vacari de (2014)
During the First Republic (1889 - 1930), numerous conflicts between oligarchs occurred in the Brazilian states. In Mato Grosso, three Disputes oligarchic marked the political life of the state in 1892, 1899 and 1906. They were due to disputes between the state elites for control of political power. In 1892, Ponce and Murtinho oligarchies together competed with the Antonio s Maria Coelho group, governor since 1899. Ponce and Murtinho won, until in 1899 disruption occurred between them, when Ponce was defeated. These two oligarchies unite again in 1906 to defeat an enemy uncommon: the governor of the state of Mato Grosso Antonio Paes de Barros, who was murdered in this episode. This research proposes to analyze the specifics of the Mato Grosso oligarchies and its consequences for the political practices in the state of Mato Grosso in the period 1892-1906. Thus, we investigated the formation and consolidation of these two oligarchies, for understand how relationships between Ponce and Murtinho oligarchies interfered in the politics of Mato Grosso. We also considered the relationship between the municipal and state (Ponce and their local chiefs) and between state and federal (connection of Ponce and Joaquim Murtinho, the interference continues, or omission of Presidents of the Republic and the use of the Verification of Credentials Committee). Was used as a theoretical literature on Community Power Structure, Coronelismo e Neo-institutionalism.